Design a Pepper Seed Drying Oven with a Capacity of 8-10 (kg/hour) - Naufal, Alban; Yosdy Nurliansyah; Rina Dwi Yani; Tri Pratomo (Politeknik Piksi Ganesha Indonesia, 2023)
The drying process of pepper seeds is still done by relying on sunlight, whereas rainy weather conditions will greatly slow down drying. Drying using an oven is done to make the pepper cleaner from dirt and efficient against the time of drying the pepper, For this reason, an oven is needed to dry pepper seeds so as not to be too dependent on weather conditions. This oven heating system uses LPG gas, a hygrometer used to estimate temperature and humidity, and a thermostat to regulate the room temperature in the oven, also equipped with an automatic lighter to make it easier to start the fire in the oven. The dried peppers that have been tested ranging from 50°C, 60°C, 70°C, 80°C, and 90°C are all dry with the longest duration of 99 minutes and the fastest time of 15 minutes.